Civilian oversight of the police in England and Wales: The election of Police and Crime Commissioners in 2012 and 2016. (March 2017) - Mawby, Rob I; Smith, Kreseda
The creation of Police and Crime Commissioners (PCCs) in England and Wales in November 2012 by the Conservative/Liberal Democrat Coalition government, replacing the former police authorities, introduced a new mechanism for civilian oversight of the police. However, the new structure has been heavily criticised, both for the election process and for the ways in which newly elected PCCs have operated. Despite these criticisms, PCCs were retained by the new Conservative government, and the scheduled round of new elections took place in May 2016. This article assesses these elections and compares them with those 2012, in terms of the election process and the attributes of the candidates and those successfully elected.